Variations In "Code-Mixing" Patterns Within Informal Language Styles Among Gen Z In South Jakarta - Evan Evan Yulzaen; Muhammad Rafly Dwieansyah; Davyna Nareshwary Putri Marfizal; Najma Putri Julianti; Fathia Najiyah (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
This study examines the phenomenon of "code mixing," popularly known asthe "Anak Jaksel" (South Jakarta youth)language style, among Generation Zin South Jakarta as of 2025. In the era of globalization, language hastransformed from a mere pragmatic communication tool into a vitalinstrument for forming cultural and social identities. This research aims tocomprehensively analyze the variations of code-mixing patterns, theunderlying sociocultural factors, and their implications for social identityconstruction within a global urban society. Using a qualitative approach andin-depth interviews, the study found that the most dominant form of codemixing is intrasentential, specifically the insertion of English lexical wordsinto Indonesian sentence structures. Common terms such as "anxious,""literally," or "make sense" are often used spontaneously, influenced bysocial circles,digitalmedia exposure, and the internet. The findings indicatethat this practice serves as a linguistic strategy to create more relaxed,comfortable, and expressive communication. Furthermore, based on SocialIdentity Theory, code mixing functions as a group identity marker that fostersa sense of belonging and confidence among Gen Z. However, the study alsoreveals a process of identity negotiation; informants consciously adjust theirlanguage by reducing code mixing and using formal Indonesian wheninteracting with lecturers or older individuals to maintain professionalismand politeness.